The ontogenetic development of Rana dalmatina Bonaparte, 1840 species (Amphibia: Ranidae) in the context of climate change - Tudor Cozari; Elena Gherasim (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
Globally, amphibians represent one of the main objects of study in the context of climate change, because the temperature variations recorded and in the Republic of Moldova also represent a major threat to their development and sustainability. For this purpose, a complex ecological study was carried out regarding the embryonic and larval development strategies of the Rana dalmatina Bonaparte, 1840, species and the main particularities related to its population structure and dynamics were described. This research allowed us to evaluate the degree of ecological plasticity of natural populations of Rana dalmatina in relation to the plurality of environmental factors, which allows us to develop suitable and safe measures for monitoring and conservation of the species.